Dynamical structure of rifle trajectories in biathlon shooting - Buchecker, M.; Sattlecker, G.; Wegenkittl, S.; Lindinger, S.; Müller, E. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Physiological-behavioral complexity emerges from the confluence of organismic, environmental and task constraints and can be assessed through tools evaluating the shape of neurobiological signals; thus, they provide a window into the organization of motor control1,2. Since a profound description of pattern dynamics in sports, and in biathlon in particular, is missing, the aim of the current study was (1) to analyze the time-varying properties of rifle motion and (2) to evaluate whether different settings or techniques would affect underlying coordinative strategies.